Case Report: A case of Culler-Jones syndrome caused by GLI2 gene mutation - Xie, Xiaomei; Wei, Youfen; Li, Ye; Wang, Junyan; Zhang, Yating; Wu, Jie; Wang, Fan (Frontiers in Pediatrics, 2025)
Culler-Jones syndrome (CJS) (OMIM: 615849) is a rare genetic condition characterized by considerable phenotypic variability. This case reports a 5-day-old male neonate who presented with postaxial polydactyly, growth restriction, and recurrent epileptic seizures. A thorough clinical workup, including laboratory investigations, imaging, and genetic analysis, resulted in a confirmed diagnosis of Culler-Jones syndrome. Peripheral blood samples collected from the proband and his parents were used for DNA extraction. Whole-exome sequencing (WES) identified a heterozygous nonsense variant in the GLI2 gene, [c.2137(exon13)G>T/p.(E713,857) (NM_001374353)], which was subsequently validated by Sanger sequencing and determined to be maternally inherited. This mutation has not been previously documented in the literature. By detailing the clinical presentation, genetic findings, and relevant context, this case report aims to broaden the known phenotypic spectrum of Culler-Jones syndrome and support clinicians in early detection and diagnosis.